COVID-19-associated pulmonary aspergillosis in a tertiary care center in Shenzhen City - Zhaofang Jiang; Shuyan Chen; Qing Zhu; Yanyu Xiao; Jiuxin Qu (Elsevier, 2022)
Objectives: The severe coronavirus disease 2019 (COVID-19) is characterized by acute respiratory distress syndrome (ARDS) and risk of fungal co-infection, pulmonary aspergillosis in particular. However, COVID-19 associated pulmonary aspergillosis (CAPA) cases remain limited due to the difficulty in diagnosis. Methods: We describe presumptive invasive aspergillosis in eight patients diagnosed with COVID-19 in a single center in Shenzhen, China. Data collected include underlying conditions, mycological findings, immunodetection results, therapies and outcomes. Results: Four of the eight patients had tested positive for Aspergillus by either culture or Next-generation sequencing analysis of sputum or bronchoalveolar lavage fluid (BALF), while the rest of patients had only positive results in antigen or antibody detection. Although all patients received antifungal therapies, six of these eight patients (66.7%) died. Conclusion: Due to the high mortality rate of CAPA, clinical care in patients with CAPA deserves more attention.